Simulation and optimization of methanol autothermal reformer for fuel cell applications - Abdul Rahman, Azmil (2006)
The physically base study for steady state model for hydrogen production using autothermal reforming of methanol is developed using commercial simulator, Aspen HYSYS 2004.1. The development of the physical model will involve rigorous thermodynamics, and the data from mathematical stoichiometry calculation of total reaction hydrogen production from methanol as a steady state validation to build an accurate steady state model and reaction conversion is 100%. The initial steady state data will be generating in Aspen HYSYS 2004.1 that uses Autothermal Reforming (ATR), Water Gas Shift (WGS) and Preferential Oxidation (PrOx) reactor analysis. Validation results show that model developed using Aspen HYSYS 2004.1 is accurate and can be used for further analysis. Heat integration is implemented to utilize an excess heat generated by ATR. Here, all the inlet streams are heated up using that excess heat. Polymer Electrolyte Membrane Fuel Cell (PEMFC) can only tolerate carbon monoxide (CO) composition that is less than 10 ppm. Therefore, one of the objective of this study is to reduce the composition of CO that will satisfy the requirement of PEMFC, while optimize the hydrogen composition. In order to do that, the clean up process that consists of WGS and PrOx is implemented. After that, the plant wide optimization is carried out and the result show that the optimum conditions of 9.43 ppm of CO and 45.45% of hydrogen can be achieved with 1.5 and 0.6 ratio of Air to Fuel (A/F) and Steam to Fuel (S/F), respectively with fuel processor efficiency of 85.80%.